2022
DOI: 10.3390/molecules27134069
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Protects against Malathion-Induced Rat Testicular Toxicity: A Possible Clue on Modulating Gut Microbiome and Inhibition of Oxidative Stress by Mitophagy

Abstract: Testicular dysfunction is caused by chronic exposure to environmental pollution, such as malathion, which causes oxidative stress, promoting cell damage. Autophagy is a key cellular process for eliminating malfunctioning organelles, such as the mitochondria (mitophagy), an eminent source of reactive oxygen species (ROS). Autophagy is crucial for protection against testicular damage. Rifaximin (RFX) is a non-absorbable antibiotic that can reshape the gut microbiome, making it effective in different gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 68 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…that had the highest levels of lipid peroxidation and the lowest concentrations of both GSH and GPx. (Omar et al, 2022b) have reported that malathion exposure significantly reduced sperm count and motility as well as serum testosterone levels when using three different concentrations (25 mg/kg, 50 mg/kg, and 100 mg/kg) when using it for two and four weeks, which is consistent with the findings of our study at a dose of 27 mg/kg (3 times/week) for 60 days of exposure to malathion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…that had the highest levels of lipid peroxidation and the lowest concentrations of both GSH and GPx. (Omar et al, 2022b) have reported that malathion exposure significantly reduced sperm count and motility as well as serum testosterone levels when using three different concentrations (25 mg/kg, 50 mg/kg, and 100 mg/kg) when using it for two and four weeks, which is consistent with the findings of our study at a dose of 27 mg/kg (3 times/week) for 60 days of exposure to malathion.…”
Section: Discussionsupporting
confidence: 92%
“…Malathion is an organophosphorus (OP) insecticide that has been shown to disrupt sperm quality and impair reproductive hormone synthesis by inducing a cascade of oxidative stress (Omar et al, 2022b). (Massoud, 2022) suggested that malathion affects the germinal and somatic cells of the testis and lowers testosterone activity, which inhibits spermatogenesis by causing Sertoli cells and germ cells to become damaged and vacuolated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondria dysfunctions suppress the β-oxidation of mitochondria and increase the production of the toxic lipid metabolism, which further adversely affects the mitochondrial dysfunction [ 102 ]. Interestingly, the gut microbiota could produce short-chain fatty acids (SCFAs), which might act as signal molecules to regulate the autophagy [ 103 , 104 ]. Therefore, the modulation of microbiota has been shown to control the machinery of autophagy against liver toxicity [ 105 ].…”
Section: Improved Mitophagy With the Modification Of Gut Microbiota F...mentioning
confidence: 99%
“…It is assumed that microbiota modify DNA methylation in a genome-specific or non-genome-specific manner. For instance, the microbiota can induce oxidative stress by generating mitochondrial reactive oxygen species (ROS) via autophagy [ 89 ]. Oxidative stress modulates DNA methylation, thereby changing gene expression.…”
Section: The Molecular Mechanisms Of Gut Microbiota On Brain Developmentmentioning
confidence: 99%